Analisis Faktor - Faktor yang Mempengaruhi Konsumen dalam Membeli Produk Susu Pasteurisasi Kabupaten Kudus (Analysis of Factors Influence Consumer’s Purchasing of Pasteurization of Milk at District Kudus) - Budi Hartono; Hari Dwi Utami; Nova Amanatullaili (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The objectives of this study was to investigate factors influence consumer decision making in purchasing pasteurized milks and to examine factors that influence consumer decision to buy its. The study was conducted at Kota subdistrict, Kudus district with consumer`s of milk pasteurization as respondents. This study was carried out in January 2010. One hundred buyers were chosen as respondent by accidental sampling method. Data were analyzed using canonical correlation. The results showed that respondents had in complex decision making and brand loyalty types. The result also indicated that factors such as demography consumer`s, motivation of needs and desired, culture, factor of group, factor of quality facility and promotion had influence the consumer`s purchasing of pasteurized milk.(Key word: Consumer purchase decision, Canonical correlation analysis, Milk pasteurization)